Social capital and health: new frontiers and old problems in a working-class neighbourhood in Naples - Calicchia, Francesco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
Rione Sanità is a neighbourhood in the Third Municipality of Naples. The only hospital in the neighbourhood, San Gennaro, after being threatened with closure by the Region for over ten years, has now been included in the Campania Region’s territorial reorganisation plan, which implements the directives of Ministerial Decree 77; and should therefore become a Community Hospital. This evolution of its role in the neighbourhood can be traced back to the great and constant work done by the Comitato San Gennaro, an expression of the neighbourhood’s protest. Does the Committee’s strength lie in a territorial social capital that has been able to fuel the protest? And in what way? And, in light of the new health reorganisation plan in the area, can this resource be used by the public administration? And if so, is there a regulatory framework in which to give formal status to its role for the Hospital and for the entire territory? In order to answer these questions, it was decided to carry out field research, using the method of participant observation as a privileged tool, and going into certain aspects in depth with semi-structured interviews with key players. Finally, using the available reference literature, we analysed the evolution and innovations that Ministerial Decree 77 is expected to bring.